Mentoring Students with Intellectual and Developmental Disabilities: Evaluation of Role-Specific Workshops for Mentors and Mentees - Agarwal, Rumi (J Autism Dev Disord, 2020)
Transitioning to post-secondary education is often challenging for students with intellectual and developmental disabilities (IDD). To address this, Florida International University, specifically FIU Embrace, piloted the Embrace Mentoring Program (EMP), which provided unique role-specific workshops to both faculty/staff mentors, and student mentees with IDD. A mixed-method design was used to analyze knowledge acquisition and participant perceptions of the workshops. Quantitative findings indicated knowledge improvement in a key area for mentors, while qualitative data demonstrated a positive response to workshop content, and highlighted areas of improvement for future workshops. Ultimately, the results from the pilot EMP demonstrated promise in supporting students with IDD towards academic and career-related goals, by providing mentorship training to both mentors and mentees.